Membangun Kesadaran Publik Terhadap Trading Berjangka Melalui Program Edukasi Interaktif “Bincang Trading 2025” - Puteri Haiza Nurisnadiah; Dermawan, Rizky (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
The development of technology and digitalization has driven increased public interest in various investment instruments, including futures trading. However, the low level of financial literacy and misinformation on social media pose serious challenges in forming a complete and responsible understanding of this instrument. In response to this issue, the interactive education program “Bincang Trading 2025” was held as an effort to increase public awareness and understanding of the fundamental aspects, risks, and practices of futures trading directly. This article uses a qualitative descriptive approach with a case study of the implementation of “Bincang Trading 2025” program in Surabaya. This program proves that a collaborative, contextual, and experience-based educational approach can be an effective strategy to increase public financial literacy in facing the complexities of the world of futures trading. Keywords: financial literacy, futures trading, interactive education, simulation, public